THE EFFECT OF THE PANDEMIC PERIOD ON MENTAL HEALTH - Baki, Esra (International Scientific Journal Vision, 2020)
During the pandemic period, the feeling most commonly experienced as a result of the epidemic that affected the whole world is the feeling of anxiety about someone’s own health or the health of his relatives. Although being a subjectively negative internal experience, anxiety is also useful because its presence at a certain level will cause the person to stay away from dangers, to be cautious, and comply with the precautions. The fact people are exposed to life threats by a virus that they cannot fully see and do not know how to function also triggers a sense of uncertainty. It causes feelings of fear and anxiety about the uncertainty created by the pandemic. Stress, as a result of the individual’s environment and situation during the pandemic period, many factors such as restriction of some habits, social distancing, quarantine period, economic problems trigger the emergence of the stress to be experienced more severely. People show a normal distribution and diversity in terms of their psychological responses to the pandemic. If it does not progress in the same way in every individual, that is, if some individuals show very severe symptoms and some individuals survive without realizing it; The psychological effects created by the pandemic process also vary between individuals. The majority of people experience a moderate level of anxiety, thus minimizing risks and maintaining their functionality. The uncertainty created by the pandemic period causes individuals to experience the feeling of stress above normal, and this is due to the pressure created by the feeling of anxiety on the individual. Dealing with the most important psychological factors caused by the pandemic process is to remember that emotions such as anxiety, fear, uncertainty and anger felt by the person are useful as long as they are not excessive and don’t eliminate the functionality of the person.